Theoretical and Numerical Study of the Time-Bandwidth Product in Resonant Cavities with Nonreciprocal Coupling - Cardea, I.; Grassani, D.; Upham, J.; Boyd, R.W.; Schulz, S.A.; K. L. Tsakmakidis; Bres, C.S. (Conference Proceedings - Lasers and Electro-Optics Society Annual Meeting-LEOS, 2020)
We present a theoretical and numerical model to show how the nonreciprocal coupling in a generalized resonator affects the balance between the reflected and intracavity power as well as the time-bandwidth product of the system. © 2020 OSA.